Genetic diversity of three size classes of seeds of Eucalyptus globulus ssp. globulus - Martins-Corder, M. P. (1998)
Variation in seed size is often observed in samples of eucalypt seeds and this leads to heterogeneous populations of plants, principally through variation in the early stages of plant development. It follows that samples of seeds more uniform in size could produce more uniform populations of plants. In studies of Eucalyptus globulus ssp. globulus it was of interest to determine whether or not the genetic diversity within a population, through the use of isozyme markers, was altered in the subpopulations developed from seeds of different size classes. A commercial sample of seed was separated by seed size into three subpopulations and the percentage germination and mean fresh weight of the seedlings were determined. Proteins extracted from leaves of the seedlings were separated by electrophoresis and tested for activity of eight different enzymes. These eight enzymes showed activity at 20 loci and mean genetic diversity and fixation index were determined using 13 of these loci. The subpopulation of the smallest seeds contained a greater proportion of abnormal seeds and had a lower percentage germination and plant weight compared to the other subpopulations. No significant differences were found in the number of alleles per locus, percentage of polymorphic loci, mean heterozygosity. The major part of the endogamy, indicated by F statistic, was found within the subpopulations: F(IS) = 0.518; F(ST) = 0.010 and F(IT) = 0.523. We conclude that the use of seeds of uniform size will lead to more uniform germination and plant growth without alteration in overall genetic diversity.